(untitled) (Pakistan Journal of Engineering, Technology and Science, 2025)
This paper presents Detect-iPro, which uses the AI to detect defects at the automotive relay box, assign weights, and track faults in real time. The system relies upon the highly precise but also fast object detection with the YOLOv8 model of deep learning and is easy to integrate with the assembly lines with the help of high-resolution imaging and a convenient graphical user interface. The continuous improvement of the processes and regulatory compliance is also possible through automated data logging as well as real-time feedback that not only ensures a better traceability but also allows the improvement of the process in question. Thorough testing in factory-conditions shows considerable improvements in accuracy, speed and efficiency, and predetermines new standards in automotive quality control. The paper is completed with the discussion of the system limitations, future research principles, and how AI can transform smart manufacturing.